DOI: 10.5353/th_b5736652
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle independent role of cyclin D3 in host restriction of influenza virus infection

Abstract: Edited by Charles E. SamuelTo identify new host factors that modulate the replication of influenza A virus, we performed a yeast two-hybrid screen using the cytoplasmic tail of matrix protein 2 from the highly pathogenic H5N1 strain. The screen revealed a high-score interaction with cyclin D3, a key regulator of cell cycle early G 1 phase. M2-cyclin D3 interaction was validated through GST pull-down and recapitulated in influenza A/WSN/33-infected cells. Knockdown of Ccnd3 by small interfering RNA significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This effect is reminiscent of the role of cyclin D3 in influenza infection, where cyclin D3 depletion resulted in increased viral production. This study also showed that cyclin D3 binds M2 protein and interferes with the M1–M2 interaction leading to defective viral assembly (Fan et al , 2017).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This effect is reminiscent of the role of cyclin D3 in influenza infection, where cyclin D3 depletion resulted in increased viral production. This study also showed that cyclin D3 binds M2 protein and interferes with the M1–M2 interaction leading to defective viral assembly (Fan et al , 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Cyclin D3 has been previously implicated in the restriction of influenza A virus through impairment of virus assembly (Fan et al , 2017). Cyclin D3 has been shown to interact with IAV protein M2, an ion channel that promotes viral replication (Pinto & Lamb, 2006; Fan et al , 2017). Interestingly, SARS‐CoV‐2 envelope (E) protein has been suggested to be an ion channel (Singh Tomar & Arkin, 2020; Xia et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ‘cell cycle’ plays a pivotal role in host‐virus interaction. Influenza viruses could escape the host restriction and facilitate their own replication through changing the cell cycle transition points 30‐32 . Therefore, these findings provide a possible clinically relevant to better understand the relationship between immune cell proliferation and viral load change.…”
Section: Discussionmentioning
confidence: 96%
“…The dual function of RED-SMU1 raises the question whether our observed antiviral effect of compounds LSP461 and LSP61 could be related not only to inhibition of viral mRNA splicing (as indicated by a reduced NS2-to-NS1 mRNA ratio upon treatment) but also to cell cycle arrest. Although this possibility cannot be formally excluded, it seems unlikely, as IAV infection per se has been shown to induce G0/G1 cell cycle arrest through inhibition of the RhoA/pRb signaling pathway (47) and down-regulation of cyclin D3 levels (48) in cultured cells. Besides, the tissue naturally targeted by IAVs (i.e., the airway epithelium) is essentially quiescent in healthy hosts (49).…”
Section: Discussionmentioning
confidence: 99%